2009
DOI: 10.1080/03601230902935154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic bacteria on the bioaccessibility of aflatoxin B1and ochratoxin A using anin vitrodigestion model under fed conditions

Abstract: In the present study, we aimed at determining the release of aflatoxin B(1) (AFB(1)) and ochratoxin A (OTA) from different food products in the gastro-intestinal tract in the absence and presence of probiotics, a possible adsorbent. The average bioaccessibility of AFB(1) and OTA without probiotics was about 90%, and 30%, respectively, depending on several factors, such as food product, contamination level, compound and type of contamination (spiked versus naturally contaminated). The six probiotic bacteria sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 24 publications
7
58
1
Order By: Relevance
“…OTA are known to cause damage in the digestive system (Kabak et al, 2009). This may altered the absorption of vitamins in the digestive tract.…”
Section: Resultsmentioning
confidence: 99%
“…OTA are known to cause damage in the digestive system (Kabak et al, 2009). This may altered the absorption of vitamins in the digestive tract.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors may affect the bioaccessibility of single and multiple mycotoxins. Variability within mycotoxin bioaccessibility values depends on the compound, food product, contamination level and way of contamination (spiked or naturally contaminated) (Kabak et al, 2009). Additionally, the diversity of in vitro digestion models used to access the bioaccessibility of mycotoxins constitutes another important challenge.…”
Section: Main Challenges In Hazard Assessment Of Multiple Mycotoxinsmentioning
confidence: 99%
“…The majority of models reported in literature are the static ones (Gil-Izquierdo et al, 2002;Hur et al, 2011;Versantvoort et al, 2005). However, more sophisticated dynamic in vitro models are also available and although more realistic, they are complex and expensive (Avantaggiato et al, 2004;González-Arias et al, 2013 (Kabak and Ozbey, 2012), AFB 1 and OTA (Kabak et al, 2009;Raiola et al, 2012;Versantvoort et al, 2005), enniatin Prosperini et al, 2013), trichothecenes T-2 and HT-2 toxin (Monaci et al, 2015). A very recent preliminary study evaluated the possible interactions that could happen when PAT and OTA co-occur in cereal-based baby foods (Assunção et al, 2016).…”
Section: Hazard Assessment Of Multiple Mycotoxinsmentioning
confidence: 99%
“…In a similar experimental system, Polivkova and co-workers (2010) observed antimutagenic effects of lycopene and tomato puree, wich was related with a significant reduction of DNA damage in mice cells assessed by the micronucleus test. Probiotics microorganisms could be used in order to amelliorate the adverse effects of exposure to aflatoxins (Kabak et al, 2009), since it was suggested that whole microbiological cells or fractions of them could adsorb mycotoxins, including the aflatoxins.…”
Section: Approaches In the Articles Regarding To The Toxicology Of Afmentioning
confidence: 99%